2021
DOI: 10.1080/20909977.2021.1900527
|View full text |Cite
|
Sign up to set email alerts
|

Combined geophysical and geotechnical investigation of pavement failure for sustainable construction of Owo-Ikare highway, Southwestern Nigeria

Abstract: Very low frequency electromagnetic (VLF-EM) and electrical resistivity methods involving 54 Schlumberger Vertical Electrical Sounding (VES) and 2-D geoelectrical resistivity imaging using dipole-dipole array were utilised along unstable (US) and stable sections (SS) of Owo-Ikare highway to establish causes of its persistent failure. Engineering evaluation of eighteen soil samples from test pits excavated on selected US and SS were investigated. VLF-EM models, geoelectric sections and 2-D resistivity structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The electrical resistivity investigation employed Schlumberger vertical electrical sounding (VES) technique with a total of forty-two sounding stations occupied across the entire area of study. The VES data were acquired using ABEM SAS 1000 terrameter with the electrode spread (AB/2) ranging 1 -200 m. This non-invasive technique presents requisite information of subsurface rock properties from varying electrode separation (Ademila, 2021;Ademila, 2022). VES measurements probe the vertical variation in resistivity distribution of geomaterials at each sounding station with depth.…”
Section: Geological and Geophysical Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical resistivity investigation employed Schlumberger vertical electrical sounding (VES) technique with a total of forty-two sounding stations occupied across the entire area of study. The VES data were acquired using ABEM SAS 1000 terrameter with the electrode spread (AB/2) ranging 1 -200 m. This non-invasive technique presents requisite information of subsurface rock properties from varying electrode separation (Ademila, 2021;Ademila, 2022). VES measurements probe the vertical variation in resistivity distribution of geomaterials at each sounding station with depth.…”
Section: Geological and Geophysical Mappingmentioning
confidence: 99%
“…Electrical resistivity techniques have been gainfully employed in engineering site to investigate and image the subsurface disposition by measuring electrical properties of geomaterials. This in turn has been used in unraveling the stratigraphic sequence of geomaterials, subsoil competence, overburden thickness, nature and distribution of geologic structures and depth to basement (Ademila et al, 2020;Ademila, 2021;Ademila, 2022). These effective noninvasive and non-destructive geophysical tools for subsurface investigation also offer information on quantitative estimates of geologic deposits, geomorphology and tectonic activity of areas (Bufford et al, 2012;Ademila, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted Vs were validated using a Cd and comparison of measured Vs in this investigation. Cd is also calculated using equation (6) [67] as the ratio of the difference between the Vspre and Vsmeas divided by SPT-N values where Vsmeas is the measured shear wave velocity, Vspred is the calculated Vs using the newly proposed regression equation for the study area, and SPT-N values are the measured SPT-N values.…”
Section: Correlation Of Vs and Spt-nmentioning
confidence: 99%
“…Moreover, the nature/type of soils, geologic sequence, and structures and water bearing units also affect the stability of civil engineering structures. These properties provide reliable information to effectively characterize the heterogeneous subsoil beneath an engineering site so as to construct successful structure [5,6]. Buildings, roads, bridges, and high ways are infrastructures that contribute significantly to the sustainable development of the town.…”
Section: Introductionmentioning
confidence: 99%
“…Road failures are related to substandard structural materials and poor plan with no consideration of the subsoil (Ademila, 2018; Integrated geophysical investigations provide the basic information of the subsurface sequence and structural disposition necessary for foundation design. Ademila, 2021 used geophysical approach to establish reasons for construction works failure in Nigeria. They reported that poor subbase materials and poor compaction during construction account for the failure of rigid pavements in Nigeria.…”
Section: Introductionmentioning
confidence: 99%